Overcoming the mucosal barrier: tetraether lipid-stabilized liposomal nanocarriers decorated with cell-penetrating peptides enable oral delivery of vancomycin - Uhl, Philipp; Sauter, Max; Hertlein, Tobias; Witzigmann, Dominik; Laffleur, Flavia; Hofhaus, Götz; Fidelj, Veronika; Tursch, Anja; Özbek, Suat; Hopke, Elisa; Haberkorn, Uwe; Bernkop-Schnürch, Andreas; et al. (Advanced therapeutics, 2021)
Despite the high medical need for oral peptide delivery, instability in the gastrointestinal tract and low mucosal permeation still impede this preferred route of administration. Herein, a liposomal nanocarrier combining two self-reliant strategies to overcome these delivery barriers is reported. This approach enables the design of a nanocarrier system with synergistic properties: tetraether lipids derived from archaea are incorporated into liposomes to provide the particles with the stability required to traverse the stomach. When the surface of the resulting inert particles is modified with cell-penetrating peptides, mucosal permeation can be achieved. The designed nanocarrier is proven effective by the high mucosal uptake of the glycopeptide antibiotic vancomycin in Ussing chamber studies. Efficacy in vivo is demonstrated in naïve rats, where a highly increased oral bioavailability is obtained for vancomycin, a drug known to be minimally absorbed. In contrast, administration of liposomes with single modification (tetraether lipids) leads to a substantially lower bioavailability. Therapeutic efficacy is proven by the antimicrobial activity of vancomycin in a Galleria mellonella and a systemic infection mouse model. The high oral bioavailability in absence of cytotoxic effects demonstrates that this nanocarrier delivery strategy might boost the oral application of macromolecular drugs in general.